Selective shortening of gold nanorods: when surface functionalization dictates the reactivity of nanostructures. Issue 44 (6th November 2020) - Khelfa, Abdelali; Meng, Jun; Byun, Caroline; Wang, Guillaume; Nelayah, Jaysen; Ricolleau, Christian; Amara, Hakim; Guesmi, Hazar; Alloyeau, Damien
Abstract : We reveal how degradation kinetics and capping agents drive the selective shortening of gold nanorods in oxidative media. Abstract : The selective shortening of gold nanorods (NRs) is a directional etching process that has been intensively studied by UV-Vis spectroscopy because of its direct impact on the optical response of these plasmonic nanostructures. Here, liquid-cell transmission electron microscopy is exploited to visualize this peculiar corrosion process at the nanoscale and study the impacts of reaction kinetics on the etching mechanisms. In situ imaging reveals that anisotropic etching requires a chemical environment with a low etching power to make the tips of NRs the only reaction site for the oxidation process. Then, aberration-corrected TEM and atomistic simulations were combined to demonstrate that the disparity between the reactivity of the body and the ends of NRs does not derive from their crystal structure but results from an inhomogeneous surface functionalization. In a general manner, this work highlights the necessity to consider the organic/inorganic natures of nanostructures to understand their chemical reactivity.